Efficacy of steviol glycoside supplementation on survival growth and blood biochemistry profiles of hybrid red tilapia (Oreochromis sp.) - Choy, Jason Min Sheng (2019)
Steviol glycoside is a healthy low calorie natural sweetener extracted from a bushy plant, Stevia rebaudiana Bertoni which is used in the human food industry. Despite extensive research conducted to investigate the properties of steviol glycoside for human consumption, only a few reports is available on its use in aquafeeds. This research aimed to investigate the potential of steviol glycoside in the diet of the fish by measuring the survival, growth index, gut short chain fatty acid and blood plasma biochemistry. Tilapia were fed diets prepared by two different methods: extrusion and compact pelletization. The effects of supplementation of 0, 1, 3 and 6% of dietary steviol glycoside on the survival, growth, blood plasma chemistry and short chain fatty acid of red tilapia were investigated. Both experiments showed that stevia had no significant effects on fish growth, proximate and short chain fatty acid composition. However, an apparent sweet smelling taste was observed while manufacturing the feeds using a common pelletizer. In addition, increasing dietary steviol glycoside level in feed made with a common pelletizer decreased hepatosomatic index (HIS) indicating stress while extruded feeds with increasing amount of dietary steviol glycoside resulted in higher viserosomatic index (VSI) indicating more fat was deposited in the viscera. Further plasma analysis between stevia-free and 6% steviol glycoside fed fish showed no significant differences in blood plasma glucose, total protein, cholesterol and triglycerides. In conclusion, dietary steviol glycoside did not give any beneficial effect to hybrid red tilapia. Inclusion of 6%, in fact, indicated stress based on the decrease in HSI and irregular changes in blood plasma biochemistry of glucose, total protein, triglycerides and cholesterol trend.